A Case of Synchronised Pupillary and Nasal Cycling: Evidence for a Central Autonomic Pendulum?. (3rd September 2017) - Bremner, Fion D.; Nordström, Jonas Gälldin
ABSTRACT: We previously reported that some healthy individuals show alternating anisocoria. We now describe one such individual who also exhibits a classic nasal cycle (alternating periods of nasal congestion and decongestion). We made measurements of his pupil asymmetry and nasal asymmetry at 21 different time points and found that these variables were always synchronised such that greater nasal airflow was invariably found on the same side as the larger pupil. We hypothesise that a common central oscillator may be responsible for co-modulating the sympathetic outflow to both nasal vessels and iris dilator muscles in some healthy individuals.